2021
DOI: 10.1186/s40709-021-00145-6
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane inhibits malignant progression of colorectal cancer via hsa_circ_0000231-mediated miR-622

Abstract: Background Sevoflurane (Sev), a commonly used volatile anesthetic, has been reported to inhibit the process of colorectal cancer (CRC). Circular RNAs (circRNAs) are revealed to participate in the pathogenesis of CRC. This study aims to reveal the mechanism of hsa_circ_0000231 in Sev-mediated CRC progression. Methods The expression of hsa_circ_0000231 and microRNA-622 (miR-622) was detected by quantitative real-time polymerase chain reaction (qRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…1 B). Studies have found that hsa_circ_0000231 affects the progression of colorectal cancer by targeting miR-622 and miR-502-5p [ 23 , 24 ]. The results of this study also found that overexpression of hsa_circ_0000231 can promote the growth of CRC cells and lead to a poor prognosis (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…1 B). Studies have found that hsa_circ_0000231 affects the progression of colorectal cancer by targeting miR-622 and miR-502-5p [ 23 , 24 ]. The results of this study also found that overexpression of hsa_circ_0000231 can promote the growth of CRC cells and lead to a poor prognosis (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review reveals that nine circRNAs may regulate this coexpression network through miRNA‐200c and miR‐622 including circ_VMA21, circ_0057481, circ_GLG1, circ_TMX4, circ_MTUS1, circ_UBXN7, circ_0119872, circ_0000231 and circ_0000211. 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 …”
Section: Discussionmentioning
confidence: 99%
“…48 Januchowski et al 49 reported that the extracellular matrix (ECM) could affect drug resistance pro- TMX4, circ_MTUS1, circ_UBXN7, circ_0119872, circ_0000231 and circ_0000211. [55][56][57][58][59][60][61][62][63] Studies show that RSAD2 is up-regulated and associated with worse relapse-free survival in breast cancer. 64 Tang et al 65 reported that the overexpression of this immune-related gene is associated with tumour grade, stage and size in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, circCELSR1 acts as a molecular sponge and promotes paclitaxel resistance by competition with miR-1252 for binding FOXR2 [9]. For circ_0000231, it was reported [10] that circ_0000231 attenuated Sevo urane aroused repression impacts on CRC development by sponging miR-622. However, the role of circ_0000231 in OC PTX-resistance remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%